In Situ Observations of the Influence of Nonlinear EMIC Waves on Relativistic Electrons in the Outer Radiation Belt - Chae‐Woo Jun; Yoshizumi Miyoshi; Tomoaki Hori; Jacob Bortnik; Larry Lyons; Khan‐Hyuk Kim; Takefumi Mitani; Takeshi Takashima; Iku Shinohara; Nana Higashio; Ayako Matsuoka; Kazuhiro Yamamoto; et al. (Geophysical Research Letters)
Abstract This study demonstrates the influence of electromagnetic ion cyclotron (EMIC) rising‐tone emissions on relativistic electrons in the inner magnetosphere using data obtained from the Van Allen Probes and Arase satellites. We find that the intense EMIC rising‐tone emissions occur during the increase in the solar wind pressures, creating favorable conditions for triggering nonlinear wave growth. The strong flux drop‐out of relativistic electrons in the parallel directions of the magnetic field, with energies of 0.2–4 MeV, was associated with the wave activity. We calculated the nonlinear triggering conditions and the minimum resonant energy of relativistic electrons interaction with EMIC waves, based on our observations. We conclude that EMIC rising‐tone emissions contribute not only to the rapid loss of MeV electrons through EMIC wave‐particle interactions while extending the resonance energy to a few MeV by broadening bandwidth via nonlinear wave growth but also to interactions with sub‐MeV electrons through the nonresonant effect.